A proposed vision for the development of academic leaders of Saudi universities in the light of sustainable leadership - Alhazmi, Maha Yahia Ahmad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the degree to which academic leaders in Saudi universities apply the dimensions of sustainable leadership from the point of view of faculty members, and to identify the requirements for developing academic leaders in the light of sustainable leadership. The study relied on the descriptive approach, and the study tool was a questionnaire that was applied to a random sample of faculty members at Umm Al- Qura University, King Abdulaziz University, and Taif University. The study concluded that the degree of application of the dimensions of sustainable leadership came to a medium degree in general, and each dimension of sustainable leadership obtained a medium degree of application, as follows: ethical behavior, strategic direction, creativity and innovation, social responsibility, development and investment of human and material resources. As for the requirements for developing academic leaders in the light of sustainable leadership, they came with a high degree of need in general, and after organizational requirements a very high degree of need was obtained, and after the personal requirements of the leader a high degree of need. A proposed vision was built to develop academic leaders in the light of sustainable leadership.